Consumer Preference for Sea Fish Consumption in Dhaka City of Bangladesh - Haque, Md Enamul; Khanom, Shahnaz; Afrad, Md Safiul Islam; Barau, Aliyu Akilu; Rafiquzzaman, SM (The Agriculturists, 2019)
Fish is traditionally complemented to rice in the diet of Bangladeshi. Thus, its daily consumption is pretty normal. Although, a number of researches have been done on river fish and its consumption, there seems a few in the public that specifically studied consumer preference for sea fish consumption in Bangladesh. This study, therefore, explores the consumers’ preference for sea fish consumption in Dhaka city of Bangladesh. A cross sectional survey design was followed to collect data from 120 respondents in four quota sampled areas of the city, namely; Uttara, Khilkhet, Mirpur and Jatrabari. The results revealed that 20 species of sea fish were usually brought to the markets patronised in the selected areas, but 17 were commonly consumed. The consumers mostly preferred Tenualosa ilisha (95.83%), Pampus chinensis (91.67%), Penaeus monodon (75.0%), Lates calcarifer (74.17%), Euthynnus affinis (62.5%) and Harpadon nehereus (58.33%) for their taste whereas, Pama pama (33.33%) and Setipinna taty (46.67%) were preferred for lower price. The average monthly household sea fish consumption was 5.49 kg. Age, level of education, gender, annual income and religious view were found to have significant positive association with household sea fish consumption. Respondents preferred sea fish for health benefits related to heart, eye-sight, nutrient enrichment, diseases protection and prevention of depression. However, irregular supply of sea fish and higher price were pointed by the respondents as the main constraining factors to sea fish consumption. Generally, Bangladesh is blessed with vast sea fish resources, but consumers’ accessibility need to be strengthened. The Agriculturists 2019; 17(1-2) 41-51